Not Too Young to Run? Age requirements and young people in elected office - Mona Lena Krook; Mary K. Nugent (Intergenerational Justice Review, 2018)
Promoting youth representation in parliaments is a growing global priority. To promote youth leadership and more inclusive politics, youth organizations in Nigeria mobilized successfully for a constitutional reform to lower the eligibility age to run for political office. In this paper, we draw on global data to assess whether lower eligibility ages will in fact lead to higher levels of youth participation. We find that lower age requirements positively affect the representation of the youngest and next youngest cohorts in parliament. We draw on qualitative interviews and gender literature to theorize that lower age limits have immediate and longer-term “mobilizing effects”, shifting the calculations of potential candidates in terms of the age at which they first decide to run for office.